QUALITATIVE ANALYSIS: IMPACT OF SOCIAL MEDIA ON THE PSYCHOLOGICAL WELL-BEING OF PAKISTANI WOMEN - Manzoor, Dr. Seema; Khan, Asif; Manzoor, Dr. Asma; Idrees, Nusrat (Journal of Peace, Development and Communication, 2023)
Today the use of social media has become part of our lives and it is no more bound by economic and geographical boundaries. It has now become the most effective means of communication across the globe. Its penetration and usage is spreading more rapidly in developing countries with a variety of uncontrolled health issues and other social disadvantages. It is also important to note that women face more problems and they are more prone to psychological disorders and social pressures. This study focuses on the Impact of social media on the psychological well-being of Pakistani women. This study is purely qualitative, based on content analysis and library research techniques by using primary and secondary data sources. The findings reveal that Pakistani women are bound to use selected online spaces due to the social and patriarchal setup observed through cultural norms and gender roles. If we conduct in-depth studies, then the empirical evidence can be explored to examine the psychological well-being of women in low-income nations and in Pakistan as well.